2018
DOI: 10.3390/ijms19092514
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy Biomarkers in Bladder Cancer: A Current Need for Patient Diagnosis and Monitoring

Abstract: Bladder Cancer (BC) represents a clinical and social challenge due to its high incidence and recurrence rates, as well as the limited advances in effective disease management. Currently, a combination of cytology and cystoscopy is the routinely used methodology for diagnosis, prognosis and disease surveillance. However, both the poor sensitivity of cytology tests as well as the high invasiveness and big variation in tumour stage and grade interpretation using cystoscopy, emphasizes the urgent need for improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 238 publications
(305 reference statements)
0
90
0
Order By: Relevance
“…Bladder cancer is the 9th most common cancer around the world with an estimated 165,000 deaths per year. 145,146 Increased number of studies indicated that circRNAs were involved in the occurrence and development of bladder cancer. [147][148][149][150] For instance, circUVRAG derived from the exon from the UV radiation resistance-associated gene (UVRAG) was highly increased in bladder cancer cells, and regulated the aggressive biological phenotype through targeting the miR-223/fibroblast growth factor receptor 2 (FGFR2) signaling pathway.…”
Section: Bladder Cancermentioning
confidence: 99%
“…Bladder cancer is the 9th most common cancer around the world with an estimated 165,000 deaths per year. 145,146 Increased number of studies indicated that circRNAs were involved in the occurrence and development of bladder cancer. [147][148][149][150] For instance, circUVRAG derived from the exon from the UV radiation resistance-associated gene (UVRAG) was highly increased in bladder cancer cells, and regulated the aggressive biological phenotype through targeting the miR-223/fibroblast growth factor receptor 2 (FGFR2) signaling pathway.…”
Section: Bladder Cancermentioning
confidence: 99%
“…Recently, several reports have highlighted the role of long non-coding RNAs (lncRNAs) as urine-based biomarkers for diagnosis of bladder cancer [1,[10][11][12][13][14][15][16][17][18][19][20][21][22]. Long non-coding RNAs are transcripts longer than 200 nucleotides that are not translated into protein [23].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Encouraged by these successes, in this study, we attempted to discover and evaluate the prediction power of a panel of lncRNAs biomarkers to discriminate bladder cancer from urocystitis. We chose totally sixteen lncRNAs as our candidate biomarkers, as suggested by previous studies [1,[10][11][12][13][14][15][16][17][18][19][20][21][22]. We conducted a study of 140 NMIBC patients and 140 urocystitis patients.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 1 more Smart Citation
“…Bladder cancer (BC) is one of the most common cancers with an estimated 165,000 deaths per year in the world [1]. Although the diagnosis and treatment techniques of bladder cancer have improved greatly in recent years, the probabilities of recurrence and progression is still high after local treatment, the 5-year survival rate and recurrence rate of high-grade BC can be approximately 5 and 80%, respectively [2][3][4], and the 5-year progression rate is about 45% [5]. Therefore, regular re-examination is required after surgery.…”
Section: Introductionmentioning
confidence: 99%